2015
DOI: 10.1038/ncomms7284
|View full text |Cite
|
Sign up to set email alerts
|

Identity of a Plasmodium lactate/H+ symporter structurally unrelated to human transporters

Abstract: Maintenance of a high glycolytic flow rate is critical for the rapid growth and virulence of malarial parasites. The parasites release two moles of lactic acid per mole of glucose as the anaerobic end product. However, the molecular identity of the Plasmodium lactate transporter is unknown. Here we show that a member of the microbial formate-nitrite transporter family, PfFNT, acts as a lactate/proton symporter in Plasmodium falciparum. Besides L-lactate, PfFNT transports physiologically relevant D-lactate, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
153
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(165 citation statements)
references
References 40 publications
11
153
1
Order By: Relevance
“…To detect not only the electrogenic anion transport of FocA and PfFNT but additionally capture the transport of the neutral acid substrate species, we used radiolabeled substrates in our assays. 3,7 Strikingly and contrary to the electrophysiology studies, we observed increasing transport rates with increasing acidity of the assay media. Apparently, neither FocA nor PfFNT exhibited closure or gating.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…To detect not only the electrogenic anion transport of FocA and PfFNT but additionally capture the transport of the neutral acid substrate species, we used radiolabeled substrates in our assays. 3,7 Strikingly and contrary to the electrophysiology studies, we observed increasing transport rates with increasing acidity of the assay media. Apparently, neither FocA nor PfFNT exhibited closure or gating.…”
contrasting
confidence: 51%
“…On the cellular level, FNTs regulate the metabolic substrate flow and fulfill vital functions, for instance the Plasmodium falciparum PfFNT that we and others identified as the malaria parasite's long-sought lactic acid transporter. 3,4 Blockade of PfFNT by small druglike molecules kills the parasites rendering PfFNT a novel antimalarial drug target. 5,6 Their physiologic relevance as well as structural peculiarities merit a deeper look into the inner workings of the FNTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A new paper by Beitz and colleagues reports the functional expression of PfFNT in yeast 20 . The authors present evidence that PfFNT transports lactate, formate and a number of other monocarboxylates via a coupled lactate:H þ symport mechanism, and is localized to the parasite surface.…”
Section: Discussionmentioning
confidence: 99%
“…The expression system used in this work has been successfully utilized before for the characterization of the Jen homologues of K. lactis (Queirós, et al 2007), C. albicans (Soares-Silva, et al 2004, Vieira, et al 2010), D. hansenii (Soares-Silva et al 2015 and Plasmodium falciparum (Wu, et al 2015). The S. cerevisiae jen1∆ ady2∆ strain (Soares-Silva et al 2011), which presents no activity for the uptake of carboxylates, was used to express the Jen permeases from C. albicans, and K. lactis as well as the ScJen1 mutant alleles.…”
Section: Discussionmentioning
confidence: 99%